The Influence of Negative Emotion on the Simon Effect as Reflected by P300 - Qingguo Ma; Qian Shang (The Scientific World Journal)
The Simon effect refers to the phenomenon that reaction time (RT) is faster when stimulus and response location are congruent than when they are not. This study used the priming-target paradigm to explore the influence of induced negative emotion on the Simon effect with event-related potential techniques (ERPs). The priming stimuli were composed of two kinds of pictures, the negative and neutral pictures, selected from the International Affective Picture System (IAPS). The target stimuli included chessboards of two color types. One was red and black the other one was green and black. Each chessboard was presented on the left or the right of the screen. The participants were asked to press the response keys according to the colors of the chessboards. It was called the congruent condition if the chessboard and the response key were on the same side, otherwise incongruent condition. In this study, the emotion-priming Simon effect was found in terms of RT and P300. Negative emotion compared with neutral emotion significantly enhanced the Simon effect in the cognitive process, reflected by a larger difference of P300 latency between the incongruent and congruent trials. The results suggest that the induced negative emotion influenced the Simon effect at the late stage of the cognitive process, and the P300 latency could be considered as the reference measure. These findings may be beneficial to researches in psychology and industrial engineering in the future.